Caracterização Tecnológica do Rejeito da Planta de Beneficiamento de Bauxita em Juruti- Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
The need for technologically characterize the waste from bauxite processing plant in Juruti-PA to identify with your position-chemical and mineralogical led to this work with a view that is necessary to know what is being generated and how much. Concern about the bauxite mining waste came up with the breaking of dams in Miraí-Gerais Gerais. This research was done by fluorescence spectrometry x-rays, the x-ray diffrac-tion and thermal analysis. The x-ray fluorescence spectrometry indicated the presence of thirteen chemical elements: iron, aluminum, silicon, tita-nium, zirconium, calcium, vanadium, potassium, chromium, sulfur, cobalt, niobium and chlorine. It is noticed that the main mineralogical phases of the waste are represented by gibbsite, hematite, kaolinite and anatase. The thermal analysis showed that the phase changes most signifi-tive only occur at a temperature above 300 °C, showing some of the waste heat stability. The results demonstrate that the components of the Juruti baux-ite beneficiation rejects exhibit appreciable characteristics of civil engi-neering, pointing to the possibility of its use to increase the strength of concrete.
Keywords: Rejeitos de Mineração; Bauxita; Juruti-PA; CNPQ::CIÊNCIAS EXATAS E DA TERRA; BIOPROSPECÇÃO E MANEJO DE RECURSOS NATURAIS DA AMAZÔNIA